Kajian kualitas air pada area budidaya kurungan jaring tancap (KJT) di Danau Tutud Desa Tombatu Tiga Kecamatan Tombatu Kabupaten Minahasa Tenggara - Tokah, Christian; Undap, Suzanne L.; Longdong, Sammy N.J. (Universitas Sam Ratulangi, 2017)
The aim of this study was to measure and assess the physical and chemical parameters of water quality in the area of ​​fixnet cage cultureat Lake Tutud Tombatu TigaVillagewhich included temperature, pH, DO, TDS, NO3, NO2, NH3 and PO4 in a different time.This research was conducted from August to November 2016. The research activities consisted of direct measurements in the field (in situ) using a Horiba instrument and laboratory analysis (ex situ) at the Agency for Industrial Research and Development Research Institute of Standardization and Industrial Manado. Determination points were done by purposive sampling which refers to the physiographic location wherever possible in order to represent or describe these waters.Water quality measured at4 stations using a Horiba at a depth of 0.5 meters from the bottom of the lake.Station I represented Inlet water, Station II where the cultivation A, Station III where the cultivation B and Station IVwhere no cultivation. The data obtained and collected were primary data i.e., measurement of physical and chemical parameters of water quality as well as watching for signs of sick fish, dead fish, and the growth of farmed fish.The results showed the water temperature ranged between 28-29 ° C, TDS 0266-0412 mg/L and chemical parameters for dissolved oxygen 2-5 mg/L, pH 7-8 and for the results of laboratory analysis, N03(0.7 - 6.3 mg/L), NO2(0001-0002 mg/L), NH3 (0180-1920 mg/L), PO4(0020-0209 mg/L). In general, the existence of water quality of lake Tutud were still in good condition except for NH3 concentrationthat exceeded quality standard limitsof Government Regulation No. 82 of 2001. Basically lake Tutud can still be used for fish farming, but the addition of new cages were not recommended. Keywords: Lake Tutud,water quality, physical parameters, chemical parameters, fix net cage